2021
DOI: 10.1097/md.0000000000023893
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of manipulation under anesthesia with or without intra-articular steroid injection for treating frozen shoulder

Abstract: Manipulation under anesthesia (MUA) combined with intra-articular steroid injection (ISI) is preferred in management of the refractory frozen shoulder (FS). This study aimed to evaluate the effect of MUA with ISI or not on pain severity and function of the shoulder. Data on 141 patients receiving MUA with primary FS refractory to conservative treatments for at least 1 month were retrospectively obtained from medical records. We performed propensity score matching analysis between patients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…For the most part, AC is diagnosed clinically. Even so, results from MRI scans, such as thickening of the axilla with decreased capsule volume, loss of sub-coracoid fat, and distension of the superior sub Scapularis bursa, can be useful [ 14 ]. In studies, ultrasound has also been found to be a reliable diagnostic tool for the detection of thickening of the Coraco Humeral ligament in AC [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, AC is diagnosed clinically. Even so, results from MRI scans, such as thickening of the axilla with decreased capsule volume, loss of sub-coracoid fat, and distension of the superior sub Scapularis bursa, can be useful [ 14 ]. In studies, ultrasound has also been found to be a reliable diagnostic tool for the detection of thickening of the Coraco Humeral ligament in AC [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is a good guide in the treatment of frozen shoulder and indicates sufficient accuracy in examining and treating frozen shoulder in diabetic patients, especially diabetic patients with poor control. Although some studies revealed that shoulder pain in diabetes was often more resistant to conventional treatment, it can be resolved without any treatment in some cases and can improve from stage one to stage three (thawing) within a few months [27] [28] [29].…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation under anaesthesia alone or in addition to arthroscopic capsular release (limited or circumferential) can be performed. However, this procedure requires expertise because of its potential complications [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%